EFFECT OF PROBLEM BASED INSTRUCTION (PBI) LEARNING METHOD ON BEHAVIOR PREVENTION OF HIV/AIDS PREVENTION IN ADOLESCENT - sri sudarsih; Ade Ayu Putriananingrum (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
HIV/AIDS is one of the health problems that concern the world today because of the increase in patient population causing health crisis in the world. The highest number of AIDS cases according to the World Health Organization (WHO) indicates that people are infected while still in middle adolescence stage. Teens need to be provided with Problem Based Instruction (PBI) method, because PBI can improve knowledge and creativity. This study aims to determine the effect of Problem Based Instruction (PBI) learning methods on prevention behavior of HIV/AIDS in adolescents. The research design used pre-experimental pre-test post-test one group design. The population is all adolescents class VIII in SMP Negeri 1 Mojoanyar Mojokerto regency as many as 180 people with a sample of 36 people using cluster random sampling technique. The results of this study indicate that there is a change of negative behavior before given Problem Based Instruction Learning (72,2%) turns into positive after given Learning Problem Based Instruction (61,1%). Wilcoxon test analysis results show that P value <Î± so that H1 accepted, meaning there is influence of Problem Based Instruction Learning to behavior prevention of HIV / AIDS transmission in adolescent. PBIs are developed to help students develop thinking and problem-solving skills, through engagement in real-life experiences and become autonomous and self-reliant learners. Schools working together with health workers are expected to create large posters or billboards about the prevention of HIV / AIDS transmission with attractive design to make it easier for students to read.